(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
This study evaluated the psychometric properties of the Pictorial Test of Cognitive Profiles (TPPC) through the internal consistency and convergent validity of the TPPC with the Brazilian version of the Personality Belief Questionnaire – Short Form (PBQ-SF). The TPPC as well as the PBQ-SF was designed as a clinical and research tool, with nine subscales, to assess personality profiles. A sample of 86 college students responded to the Brazilian version of the PBQ-SF and the TPPC. The results showed satisfactory levels for estimating the reliability (Cronbach’s alpha) of the TPPC test (alpha = .93). Overall, the findings demonstrate the convergent validity for the TPPC, suggesting that it is also a practical tool to evaluate cognitive profiles of personality as well as the PBQ-SF.